2021
DOI: 10.1111/josh.13120
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Perceptions of and Experiences with Student Menstruation in the School Setting

Abstract: BACKGROUND: Menstrual hygiene management is an important public health issue for adolescents. The objective of this study was to explore teacher perceptions and experiences addressing adolescent menstruation experiences at school and examine their perception of the impact of menstruation on student learning. METHODS:Teachers in a Midwest school district participated in an online survey about their perceptions of adolescent school-based menstruation experiences, including: experience and comfort-level with prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…Most school nurses in Missouri think that teachers and staff in their schools are comfortable speaking with students about MHM, but they also believe that teachers and staff need more professional development on how to talk to students about their MHM. These findings align with Huseth‐Zosel and Secor‐Turner's 13 results, who concluded that teachers need more education on how to address student menstruation experiences more positively to support their learning.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Most school nurses in Missouri think that teachers and staff in their schools are comfortable speaking with students about MHM, but they also believe that teachers and staff need more professional development on how to talk to students about their MHM. These findings align with Huseth‐Zosel and Secor‐Turner's 13 results, who concluded that teachers need more education on how to address student menstruation experiences more positively to support their learning.…”
Section: Discussionsupporting
confidence: 87%
“…School nurses are on the frontlines of caring for students, helping ensure they can attend school all day. A few qualitative studies about MHM in schools have involved school nurses 10 and adolescents, 11,12 as well as a quantitative study of teachers 13 . One study assessing elementary school nurses' comfort level talking with students about menstruation found that nurses desire more professional development in this arena 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,37,72 In addition, strengthening collaborative approaches between stakeholders such as the ministry of education and health, increasing human power professionals with knowledge of adolescent and youth health, structuring and strengthening schools set up for guidance counseling activities, and mainstreaming in the curriculum based on level of education keeping hierarchy and coherency of ideas will play a large role in alleviating the problem at varies level. Similarly, reproductive health programs should aim to raise awareness among parents, teachers, and policymakers about the importance of integrating adolescent and youth health 57,36,[76][77][78][79][80][81][82][83][84] through targeted training, experience sharing, comparative interventional research, and the generation of scientifically based evidence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the United Kingdom (UK), 88% of teachers surveyed (n = 789) perceived that girls' cycles affected school attendance, personal performance, confidence, mood and attitude (Brown et al, 2022). Equally in the United States of America (USA), 81% of teachers (n = 209) believed that menstrual embarrassment and poor OM health impacts learning because of difficulty with focusing, absences, and anxiety (Huseth-Zosel and Secor-Turner, 2022).…”
Section: Current State Of Menstrual Health Educationmentioning
confidence: 99%